Fractional integration and cointegration in US financial time series data - Guglielmo Maria Caporale; Luis A. Gil-Alana (Deutsches Institut für Wirtschaftsforschung (DIW), 2011)
This paper examines several US monthly financial time series data using fractional integration and cointegration techniques. The univariate analysis based on fractional integration aims to determine whether the series are I(1) (in which case markets might be efficient) or alternatively I(d) with d < 1, which implies mean reversion. The multivariate framework exploiting recent developments in fractional cointegration allows to investigate in greater depth the relationships between financial series. We show that there exist many (fractionally) cointegrated bivariate relationships among the variables examined.
Keywords: C22; G10; 330; fractional integration; long-range dependence; fractional cointegration; financial data; Finanzmarkt; Zeitreihenanalyse; Kointegration; Effizienzmarktthese; Mean Reversion; Schätzung; USA